The swords of glass - Corgiat, Sylviane (Humanoids, 2015)
Yama lives a happy and peaceful life as the daughter of the village chief, until one day a glass sword falls from the sky. The mysterious blade initially towers over the young girl, but she soon discovers that her fate is entwined with it, ultimately revealing her vital role in an ancient prophecy of epic proportions.